Pengaruh Strategi Pemasaran Terhadap Pebingkatan Penjualan Jamur Tirm Pada Omah Jamur Didesa Baru Kecamatan Mestong - Zakiatul Fakhiroh; Arsa Arsa; Ahmad Syahrizal (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This thesis entitled The Influence of Marketing Strategy on Increasing Oyster Mushroom Sales at Omah Mushrooms in Baru Village, Mestong District and aims to determine the effect of marketing strategy, product, price, place, promotion on increasing oyster mushroom sales in Baru village, Mestong sub-district in a quantitative descriptive manner regarding. This research is expected to provide benefits to writers, academic institutions related to increasing oyster mushroom sales, as well as being a source of information for SMEs to find out what the marketing strategy is. Based on the results of the research that has been done, data obtained from product, price, place, and promotion variables on increasing sales, The product has a significant effect on the increase in oyster mushroom sales. This is indicated by the X1 regression coefficient of 0.295. The significant value of the product variable is 0.003, which means it is less than 0.05. The value of tcount > ttable or 3.092 > 1.987, thus indicating that the product has a significant effect on oyster mushroom sales in Baru Village, then Ha is accepted and Ho is rejected. Prices have a significant effect on increasing oyster mushroom sales because this is indicated by the X2 regression coefficient of 0.278. The significant value of the price variable is 0.004, which means it is less than 0.05. The value of tcount > ttable or 2.573 > 1.987 then Ha is accepted and Ho is rejected. A significant place on the sale of oyster mushrooms in the Baru Village is due to the X3 regression coefficient of 0.229. The significant value of the price variable is 0.008, which means it is less than 0.05. The value of tcount > ttable or 2.697 > 1.987, thus indicating that location has a significant effect on the sale of oyster mushrooms in Baru Village, so Ha is accepted and Ho is rejected. A significant promotion of the sale of oyster mushrooms in the New Village is due to the X4 regression coefficient of 0.132. The significant value of the price variable is 0.014, which means it is less than 0.05. The value of tcount > ttable or 3.327 > 1.987, thus indicating that promotion has a significant effect on oyster mushroom sales in Baru Village.